2018
DOI: 10.1111/1346-8138.14749
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators causing cutaneous chronic itch in some diseases via transient receptor potential channel subfamily V member 1 and subfamily A member 1

Abstract: Chronic itch with an itch–scratch vicious circle is a significant problem in a large amount of diseases. Some of these diseases, such as psoriasis, atopic dermatitis, prurigo nodularis, Sézary syndrome, uremic pruritus, diabetes and jaundice, are common. For a very long time, chronic itch has been a thorny problem with few effective treatments. Because of this, itch researchers and dermatologists seek to find the mechanisms among chronic itch, inflammatory cytokines and neurons. As an immediate area of researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 61 publications
(133 reference statements)
1
38
0
Order By: Relevance
“…The signal is transmitted from afferent C terminal nerve fibers to neurons in the dorsal root ganglion and then spreads to the cerebral cortex resulting in pruritus. 34,35 In this study, there was a strong correlation between serum level of IL-2 and severity of RP (r = 0.750; p = 0,000). The results of the study are consistent with Fallahzadeh et al (2011), which reported a significant correlation between serum level of IL-2 and the severity of RP (p <0.0001).…”
Section: Chorazyczewska Et Al (2016) Reported Xerosissupporting
confidence: 52%
“…The signal is transmitted from afferent C terminal nerve fibers to neurons in the dorsal root ganglion and then spreads to the cerebral cortex resulting in pruritus. 34,35 In this study, there was a strong correlation between serum level of IL-2 and severity of RP (r = 0.750; p = 0,000). The results of the study are consistent with Fallahzadeh et al (2011), which reported a significant correlation between serum level of IL-2 and the severity of RP (p <0.0001).…”
Section: Chorazyczewska Et Al (2016) Reported Xerosissupporting
confidence: 52%
“…Brain-type natriuretic peptide (BNP) is a surrogate marker of volume overload; in addition, BNP and its receptor have also been found in transient receptor potential (TRP) vanilloid 1 (TRPV1)–expressing neurons [ 38 , 39 ]. The TRPV1-expressing neuron transmit itch sensation from the peripheral C-fiber to the central nervous system [ 40 ]. Therefore, the increase of BNP with volume overload may have a role in itching transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous literature reports that inflammatory mediators are highly associated with immune alterations in the initiation and development of chronic inflammatory diseases [ 8 , 9 ]. Interleukin- (IL-) 17A mediates the early inflammatory stages of wound repair and may hinder normal healing [ 10 ] as evidenced by the application of IL-17 suppressive antibody that reverses delayed wound closure in leptin-deficient ob/ob mice [ 11 ].…”
Section: Introductionmentioning
confidence: 99%